Frequency of Depression, Anxiety and Stress among Medical Students of Rawalpindi and Islamabad - Hafsah Gul Khattak, Hafsah Arshad, Kinza Anwar, Saeeda Taj, Maliha Iftikhar, Saif Ilyas, Mohammad Qasim Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To find out frequency of depression, anxiety and stress among medical undergraduate students. Methodology: A descriptive cross-sectional survey was conducted in medical colleges of Rawalpindi and Islamabad from January 2021 to June 2021. After approval from institutional ethical committee, sample size was calculated by using open epitool and calculated sample size was 356. Non-probability convenient sampling technique was used for data collection. The participants of age 17 and 26 years, healthy adults and both genders were included in the study. Students who were married, with disability, taking any sedatives and diagnosed with psychological disorders or illness were excluded. Written consent was taken from each participant. Data was collected by using semi-structured questionnaire which comprised of two sections, first part included demographic information and second part included DASS-21 questions. Data was analyzed by using SPSS 24. Results: The overall mean age of sample was 21.14 ± 3.6 years with a range: 17-26 years. Majority of the study participant were females 202 (56.7%) while 154 (43.3%) were males. Depression was found in 67.4%, anxiety in 62.6% and stress in 72.5% undergraduate medical students. Depression, anxiety, and stress was more prevalent among females in comparison with male gender. Conclusion: The current study indicates depression, anxiety and stress were highly prevalent among medical students. For better performance in studies there is a need to take early measures to prevent mental health problem among students. Keywords: Anxiety, Depression, Medical students, Stress